Blood oranges - Kiernan, Caitlín R. (Roc, 2013)
"My name's Quinn. If you buy into my reputation, I'm the most notorious demon hunter in New England. But rumors of my badassery have been slightly exaggerated. Instead of having kung-fu skills and a closet full of medieval weapons, I'm an ex-junkie with a talent for being in the wrong place at the right time. Or the right place at the wrong time. Or...whatever. Wanted for crimes against inhumanity I (mostly) didn't commit, I was nearly a midnight snack for a werewolf until I was "saved" by a vampire calling itself the Bride of Quiet. Already cursed by a werewolf bite, the vamp took a pint out of me too. So now...now, well, you wouldn't think it could get worse, but you'd be dead wrong"--